(untitled) (Bangladesh Journal of Agricultural Research, 2014)
A field experiment was conducted in the experimental field of Genetics and Plant Breeding Department, Sher-e Bangla Agricultural University, Dhaka, Bangladesh to study variability in 10 F4 lines obtained through intervarietal crosses along with 8 released varieties of Brassica rapa. Significant variation was observed among all the genotypes for all the characters studied. Considering genetic parameters high genotypic co-efficient of variation (GCV) was observed for number of secondary branches per plant, siliquae per plant, yield per plant, whereas days to maturity showed very low GCV. High heritability with low genetic advance in percent of mean was observed for days to maturity which indicated that non-additive gene effects were involved for the expression of this character and selection for such trait might not be rewarding. High heritability with moderate genetic advance in percent of mean was observed for plant height and days to 50% flowering indicating that this trait was under additive gene control and selection for genetic improvement for this trait would be effective. Considering, inter genotypic variability, heritability, and genetic advance, % coefficient of variation and other agronomic performance G2, G14, G18, G1, G9, G12, G16, G17 may be considered to be better parents for future uses in hybridization programme. DOI: http://dx.doi.org/10.3329/bjar.v39i2.20426 Bangladesh J. Agril. Res. 39(2): 227-241, June 2014